IMPROVING STUDENT'S MATHEMATIC REFLECTIVE THINKING ABILITY THROUGH THE IMPROVE LEARNING MODEL - Sri Apriatni; Hepsi Nindiasari; Khaeroni Khaeroni (Universitas Muhammadiyah Tangerang, 2022)
Several studies show that the learning process with a metacognitive approach helps students develop their reflective thinking skills. One of the IMPROVE syntaxes is asking metacognitive questions. This study aims to describe the influence of the IMPROVE learning model on students' mathematical reflective thinking abilities. For this reason, this study uses a quantitative approach with descriptive analysis techniques after comparing two groups of data according to the non-equivalent control group design. The study involved several students of class X IPA at MAN 2 Serang City as a population consisting of two study groups as samples. The data collection technique uses the Mathematical Reflective Thinking Ability Test (KBRM) instrument which contains six indicators. The application of the IMPROVE learning model, based on the results of the study, was proven to have a positive and significant influence on increasing students' mathematical reflective thinking skills. Also, the mathematical reflective thinking ability of students who apply the IMPROVE learning model is in the fairly good category, while the mathematical reflective thinking ability of students who apply ordinary learning is in the poor category. The achievement of each indicator of students' mathematical reflective thinking skills who apply IMPROVE learning is in the good category on 2 question indicators, fairly good category on 2 question indicators and not a good category on 2 question indicators out of a total of 6 indicators of mathematical reflective thinking ability questions